Work Cultural-Life Balance: A Phenomenological Study of Balinese Female Accountant in the Banking Sector - Vidyantari, Putu Kemala; Sudana, I Putu; Wirajaya, I Gde Ary; Suprasto, Herkulanus Bambang (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
This research covers deep understanding about how Balinese women deal on being an accountant in banking industry amidst their responsibilities in the cultural traditions. This research is a qualitative research with phenomenological approach. The purpose of this research is to interpret the experiences of Balinese women who work as an accountants in the banking sectors, in serving a dual roles and under what conditions they interpret it. Expansionist theory is used as a theoretical lens in interpreting the themes that arise in this study, after extracting its meaning. Data collection was acquired through in-depth interviews with three informants. Then, the data was analysed using Interpretative Phenomenology Analysis (IPA). The analysis showed four themes that emerged from the meaning of the subject’s experiences. There are four themes in this study, including joyful living, blessing, self-proud, and time management. Time management is one theme that emerges beyond concepts dictated in expansionist theory . Keywords: Balinese women, banking accountant, work cultural-life